A Comprehensive Inquiry of Injection Safety among Varied Healthcare Institute: Prioritizing Patient Safety and Adherence - Sanjaykumar Dabhi; Niraj B. Pandit; Tulsi S. Dabhi (Indian Journal of Public Health, 2025)
Patients and health-care providers are at significant risk of both infectious and noninfectious adverse effects due to the hazardous nature of injection techniques. According to the International Physical Activity and the Environment Network study findings, 3–6 billion injections are administered annually in India. Remarkably, studies imply that every year, at least 50% of injections performed globally are harmful. Aim of the study is to examine the overall effectiveness of the existing infrastructure and systems within health-care facilities in facilitating safe injection practices. A descriptive survey approach was used where total 26 healthcare facilities were observed and healthcare worker were interviewed. The tool consists of observational checklist. Several aspects of injection safety were found to be satisfactory in both government and private health-care facilities city. Nevertheless, opportunities for improvement exist, warranting specific measures. The implementation of regular in-service educational training sessions is crucial.